2016
DOI: 10.1590/1678-4324-2016160393
|View full text |Cite
|
Sign up to set email alerts
|

Elicitation Enhanced the Production of Phenolic Compounds and Biological Activities in Hairy Root Cultures of Bitter melon ( Momordica charantia L.)

Abstract: Momordica charantia (Cucurbitaceae) is an important vegetable and also medicinal crop which produces the bioactive compounds for various biological activities with potential uses in human health DPPH (84 and 78%), reducing potential (0.53 and 0.48), phosphomolybdenum (3.6 and 3.2 mg/g)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Overall, elicitation with MeJA caused significant increases in sinapic, ferulic, and caffeic acids and in quercetin (Figure 3). This increased production of phenol derivates was also obtained when applying elicitors to roots of bitter melon (Chung et al, 2016) and stevia plants (González-Chavira et al, 2018). Finally, sterile filtrates of Verticillum non-alfalfae significantly increased PAL activity in hop cell lines (Kunej et al, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…Overall, elicitation with MeJA caused significant increases in sinapic, ferulic, and caffeic acids and in quercetin (Figure 3). This increased production of phenol derivates was also obtained when applying elicitors to roots of bitter melon (Chung et al, 2016) and stevia plants (González-Chavira et al, 2018). Finally, sterile filtrates of Verticillum non-alfalfae significantly increased PAL activity in hop cell lines (Kunej et al, 2020).…”
Section: Discussionmentioning
confidence: 64%
“…In this respect, Ismail et al 88 , found that total flavonoid and phenolic contents were higher in hairy root cultures of Lactuca sativa as compared to the non-transformed ones. Hairy root cultures of Momordica charantia were elicited with jasmonic acid and salicylic acid to enhance biomass accumulation and phenolic compound production 89 . The rolB gene was introduced in Vitis amurensis cells and the rolB-transformed calli are able of producing up to 3.15% dry weight of resveratrol 90 .…”
Section: Enhancementmentioning
confidence: 99%
“…In cucurbits, many works have demonstrated the valuable production of bioactive compounds in tissue culture. In C. anguria, M. charantia, and M. dioica, the production of phenolic compounds in transgenic and nontransgenic roots was demonstrated to be efficient, with the production being higher in transgenic versions of the three species [254][255][256][257]. In vitro cultures with jasmonic and salicilyc acids enhanced polyphenol production in M. charantia [258].…”
Section: Tissue Culturementioning
confidence: 99%